Immune Tolerance Maintained by Cooperative Interactions between T Cells and Antigen Presenting Cells Shapes a Diverse TCR Repertoire - Best, Katharine; Chain, Benny; Watkins, Chris (Frontiers in Immunology, 2015)
The T cell population in an individual needs to avoid harmful activation by self-peptides while maintaining the ability to respond to an unknown set of foreign peptides. This property is acquired by a combination of thymic and extra-thymic mechanisms. We extend current models for the development of self/non-self discrimination to consider the acquisition of self-tolerance as an emergent system level property of the overall T cell receptor repertoire. We propose that tolerance is established at the level of the antigen presenting cell/T cell cluster, which facilitates and integrates co-operative interactions between T cells of different specificity. The threshold for self-reactivity is therefore imposed at a population level, and not at the level of the individual T cell/antigen encounter. Mathematically, the model can be formulated as a linear programming optimisation problem, which can be implemented as a multiplicative update algorithm which shows a rapid convergence to a stable state. The model constrains self-reactivity within a predefined threshold, but maintains the diversity and cross reactivity which are key characteristics of human T cell immunity. We show further that the size of individual clones in the model repertoire remains heterogeneous, and that new clones can establish themselves even when the repertoire is stable. Our study combines the salient features of the “danger” model of self/non-self discrimination with the concepts of quorum sensing, and extends repertoire generation models to encompass the establishment of tolerance. Furthermore, the dynamic and continuous repertoire reshaping which underlies tolerance in this model suggests opportunities for therapeutic intervention to achieve long-term tolerance following transplantation.